Transfusion Thresholds, Quality of Life, and Current Approaches in Myelodysplastic Syndromes - Ioannis Koutsavlis (Anemia)
Hemoglobin thresholds and triggers for blood transfusions have changed over the years moving from a higher to a lower level. This review article summarizes the current evidence of transfusion thresholds in the hospitalized as well as in the outpatient setting and particularly in myelodysplasia. Fatigue is the main reported symptom in this group of patients and current clinical trials are looking for a more liberal approach of red cell transfusion and the effect on quality of life as opposed to the restrictive strategy used in the critical care setting. Practical considerations, the cost effectiveness of this strategy in addition to the possible complications, and the use of quality of life questionnaires have also been reviewed.